Relationship between dental anxiety and pain perception during scaling in periodontally healthy subjects - Shrestha, Priti; Shakya, Sonika; Poudyal, Sijan; Dhami, Bhageshwar (Journal of Chitwan Medical College, 2021)
Background: Dental pain, anxiety and fear experience are the factors that discourage the demand for treatment. Dental treatment influences patients by causing stress and reminding them of unpleasant memories which often leads to the postponement of dental treatment deteriorating the periodontal health.Research showed that dental anxiety, fear and apprehensive anticipation of potential threats cause patients to cancel, miss, or arrive late for dental appointments. The aim of the study was to evaluate patients’ pain perception during scaling and its relationship with dental anxiety. Methods: A cross sectional study was conducted in 200 dental patients from March 2021 to June 2021 at Kist Medical College and Hospital.Pain levels after scaling were assessed with a visual analog scale (VAS) and an anxiety questionnaire consisting of seven questions, each with five possible answers. Data analysis was done with SPSS 21 using descriptive and inferential statistics. Results: The mean VAS score for the entire group was 26.70±17.73 and for women and men were 28.68±17.70 and 24.75±17.64, respectively. The difference in mean VAS scores between women and men was statistically significant (p= 0.000). The mean anxiety score for the whole study population was 12.21±4.32.The questionnaire score was similar in women 13.46±4.55 and 10.99±3.71 in men (p =0.117). Conclusions: An understanding of the presence of the anxiety and fear helps dentists to grasp what patients feel about dental treatment procedures and aid dentist efforts to enhance patients care.